The Relationship between the Oil Price Shocks and the Stock Markets: The Example of Commonwealth of Independent States Countries - Syzdykova, Aziza (International Journal of Energy Economics and Policy, 2018)
One can find many studies in the literature which examine the relationship between the oil price shocks and the macroeconomic activities. Moreover, we witness an increase in the number of studies which examine the effect of recent price fluctuations on the stock prices and returns. This work studies the relationship between the crude oil price shocks and the stock prices in Russia, Kazakhstan and Ukraine, all members of Commonwealth of Independent States (CIS), in the period of 2010:01-2017:04 using the autoregressive distributed lag (ADL) cointegration test. Empirical results show that the crude oil price shocks and the fluctuations in the stock prices are cointegrated. Furthermore the results show that the rebalancement process is asymmetrical in the long run. Keywords: Oil price shocks, Stock price, Threshold cointegration test, CIS countries JEL Classifications: G12, Q4, Q43 DOI: https://doi.org/10.32479/ijeep.7020